Correlation of Filling Fitness for Discharge Summary of Inpatient with the Health Ministerial Regulation Number 269 Year 2008 in Baptis Hospital, Batu City, Indonesia - Farah Adiba; Adi Santoso; Soraya (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2020)
The summary of returning patients is a summary of all patient care and treatment periods as has been attemptedby health workers and related parties. This sheet should be signed by the treating physician. The patientsummary returns reflect all the important information that concerns the patient and can serve as a basis forfurther action. Based on PERMENKES 269 / MENKES / PER / III / 2008 in stage 4 states that the homesummary must be made by doctors and dentists who treat patients. Therefore, the summary of patients returninghome is said to be still not good because the filling in the Medical Resume that has not been filled completely.This study uses Descriptive research, which is one type of research method that tries to describe and interpretthe object in accordance with what it is. The method used in data collection is interview and observation. Thisstudy aims to review the suitability of filling patient summary returns on the inpatient medical records file atBaptist Batu Hospital. The data used are medical record data file of inpatients in January-March 2017. Theresults showed that the highest percentage in the filling summary of patients back home that is as much as 100%exist in the patient identity variable. The completeness of the completion of the outpatient patient summary formfound at inpatient in January had reached 84%, February 86%, and March reached 87%.Keyword : Patien home summary, conformity